Factors Affecting Indonesian Corporate Risk - Mauliddini Nadhifah; Susi Dwi Mulyani (Universitas Negeri Semarang, 2024)
Purpose: To investigate how political relations, sustainability performance, and information quality affect company tax risk in Indonesia, as well as how corporate governance influences these three variables moderatingly. Method: The research examined a sample of 41 manufacturing companies that were listed on the Indonesia Stock Exchange between 2017 and 2021. Purposive sampling is the approach utilized for data collection, and panel data moderation regression is the analytical tool. Findings: The results show that sustainability performance and corporate governance have a negative effect on tax risk, while political relations and the quality of internal information have no effect on tax risk. Corporate governance as a moderator is unable to strengthen the negative influence of political relations, sustainability performance, or the quality of internal information on tax risk. Novelty: There is not much previous research that examines tax risk, while some research has used tax risk as an independent influencing factor. Tax risk is rarely studied due to the lack of previous research and issues that come to the surface.